Development of a greenhouse-based inoculation protocol for the fungus Colletotrichum cereale pathogenic to annual bluegrass (Poa annua) - Lisa A. Beirn; Ruying Wang; Bruce B. Clarke; Jo Anne Crouch (PeerJ, 2015)
The fungus Colletotrichum cereale incites anthracnose disease on Poa annua (annual bluegrass) turfgrass. Anthracnose disease is geographically widespread throughout the world and highly destructive to cool-season turfgrasses, with infections by C. cereale resulting in extensive turf loss. Comprehensive research aimed at controlling turfgrass anthracnose has been performed in the field, but knowledge of the causal organism and its basic biology is still needed. In particular, the lack of a reliable greenhouse-based inoculation protocol performed under controlled environmental conditions is an obstacle to the study of C. cereale and anthracnose disease. Our objective was to develop a consistent and reproducible inoculation protocol for the two major genetic lineages of C. cereale. By adapting previously successful field-based protocols and combining with components of existing inoculation procedures, the method we developed consistently produced C. cereale infection on two susceptible P. annua biotypes. Approximately 7 to 10 days post-inoculation, plants exhibited chlorosis and thinning consistent with anthracnose disease symptomology. Morphological inspection of inoculated plants revealed visual signs of the fungus (appressoria and acervuli), although acervuli were not always present. After stringent surface sterilization of inoculated host tissue, C. cereale was consistently re-isolated from symptomatic tissue. Real-time PCR detection analysis based on the Apn2 marker confirmed the presence of the pathogen in host tissue, with both lineages of C. cereale detected from all inoculated plants. When a humidifier was not used, no infection developed for any biotypes or fungal isolates tested. The inoculation protocol described here marks significant progress for in planta studies of C. cereale, and will enable scientifically reproducible investigations of the biology, infectivity and lifestyle of this important grass pathogen.